(untitled) (MASKAY, 2017)
A set of statistical tests is proposed, and with them it is evaluated three pseudorandom number generators PRNGs and two pseudorandom bit sequence generators PRBSs, which could be applied in the process of energy dispersion. With the generators analyzed is reached to the conclusion that none exceeds all statistical tests proposed.